FAITH, REASON, AND CULTURE: An Essay in Fundamental Theology: Karuvelil George - Franklin, Kuzhandai Easu (Journal of Dharma, 2022)
Faithful to the exhortation of Pope St. John Paul II in his Encyclical, Fides et Ratio, George Karuvelil, in his latest book, Faith, Reason, and Culture: An Essay in Fundamental Theology, aims at furnishing a ‘rationality of faith’ – justification of religion in general and Christianity in particular – against the backdrop of the challenge of modernism and its offshoots such as pluralism, scientism, secularism, atheism as well as the current relativist postmodern culture. For this purpose, the author calls to his aid several contemporary philosophies/arguments, especially those that endorse existential reasons and produce a new solution to the above-mentioned contemporary challenges under the umbrella term, ‘Fundamental Theology,’ which he claims the twentieth-century successor to the traditional ‘Natural Theology’. The book is a fresh contribution to the literature on religious epistemology.